2021
DOI: 10.1155/2021/7494144
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of OmpA and Rz/Rz1 of Lytic Bacteriophage from Surabaya, Indonesia

Abstract: A good strategy to conquer the Escherichia coli-cause food-borne disease could be bacteriophages. Porins are a type of β-barrel proteins with diffuse channels and OmpA, which has a role in hydrophilic transport, is the most frequent porin in E. coli; it was also chosen as the potential receptor of the phage. And the Rz/Rz1 was engaged in the breakup of the host bacterial external membrane. This study aimed to analyze the amino acid of OmpA and Rz/Rz1 of lytic bacteriophage from Surabaya, Indonesia. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…A 4 μL sample of each PCR product was electrophoresed on a 2% agarose gel at 100 volts for 30 min. The developing bands were visualized using a UV transilluminator (Sjahriani et al 2021b).…”
Section: Agarose Gel Electrophoresismentioning
confidence: 99%
See 2 more Smart Citations
“…A 4 μL sample of each PCR product was electrophoresed on a 2% agarose gel at 100 volts for 30 min. The developing bands were visualized using a UV transilluminator (Sjahriani et al 2021b).…”
Section: Agarose Gel Electrophoresismentioning
confidence: 99%
“…Purification and sequencing of DNA were conducted according to previous report (Thung et al 2017;Sjahriani et al 2021b). They were demonstrated using Thermo Fisher Scientific, California, USA.…”
Section: Purification and Sequencing Of Dna Bacteriophagementioning
confidence: 99%
See 1 more Smart Citation
“…Phage infection poses a selective pressure for the bacteria to lose the AMR transporters and become sensitive to antibiotics. Surface modifications can also indirectly impact bacterial fitness and antibiotic tolerance [ 157 , 158 ]. Westra et al demonstrated that Pseudomonas aeruginosa PA14 evolves immunity to phage DMS3vir under high-phage conditions through loss of the pilus [ 159 ], which can impair biofilm formation and, therefore, may reduce antibiotic tolerance [ 142 , 160 , 161 , 162 ] ( Figure 3 B).…”
Section: Lytic Phages and Antibiotic Susceptibilitymentioning
confidence: 99%